Efficient synthesis of tungsten oxide hydrate-based nanocomposites for applications in bifunctional electrochromic-energy storage devices. (9th March 2018) - Chang, Xueting; Hu, Ruirui; Sun, Shibin; Lu, Tong; Liu, Tao; Lei, Yanhua; Dong, Lihua; Yin, Yansheng; Zhu, Yanqiu
Abstract: In this work, we realized the large-scale synthesis of WO3 · H2 O nanoflakes (NFs), g-C3 N4 /WO3 · H2 O nanocomposite (NC) and graphene (G)/WO3 · H2 O NC via a sonochemical process with tungsten salt as the precursor, g-C3 N4 or G sheets as the supports, and distilled water as the solvent. Both the g-C3 N4 /WO3 · H2 O NC and G/WO3 · H2 O NC exhibited much better electrochromic (EC) performance (higher coloration efficiencies and faster response times) than that of the WO3 · H2 O NFs. Using the WO3 · H2 O-based materials as electrode materials, EC batteries that integrate the energy storage and EC functions in one device have been assembled. The energy status of the EC batteries could be visually indicated by the reversible color variations. Compared with the plain WO3 · H2 O-based EC batteries, the NC-based EC batteries possessed a lower color contrast between the charged and discharged conditions but much longer discharge durations. The EC batteries could be quickly charged in a few seconds by adding H2 O2, and the charged batteries exhibited significantly-enhanced discharging durations in comparison with the initial ones. The g-C3 N4 /WO3 · H2 O NC-EC batteries charged by a small amount of H2 O2 could produce a long discharging duration up to 760 min.